2008
DOI: 10.1002/ajmg.b.30629
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome 4q31‐34 panic disorder risk locus: Association of neuropeptide Y Y5 receptor variants

Abstract: There is strong evidence for a genetic contribution to the pathogenesis of panic disorder, with a recent linkage study pointing toward a risk locus on chromosome 4q31-q34 [Kaabi et al., 2006]. Since the neuropeptide Y (NPY) system has been reported to be involved in the pathophysiology of anxiety and in particular panic disorder and the genes coding for NPY Y1, Y2, and Y5 receptors are located in the suggested risk region (4q31-q32), variants in the NPY, NPY Y1, Y2, and Y5 genes were investigated for associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(30 citation statements)
references
References 39 publications
2
28
0
Order By: Relevance
“…The observed female-predominant influence of the ADORA2A 1976TT genotype on increased startle response dependent on caffeine intervention and anxiety-related emotional stimulation is in accordance with a higher prevalence and also a higher heritability of AS or anxiety disorders, respectively, in female patients (Jang et al, 1999;Weissman et al, 1997) as well as with previous genetic findings restricted to female patients with anxiety and affective disorders (eg, Deckert et al, 1999;Domschke et al, 2004Domschke et al, , 2007Domschke et al, , 2008a). Also, there are first reports of a potentially gender-differential effect of caffeine in animal models as well as in humans, with, however, still inconsistent conclusions (eg, Botella and Parra, 2003;Fisher and Guillet, 1997;Noschang et al, 2009).…”
Section: Discussionsupporting
confidence: 83%
“…The observed female-predominant influence of the ADORA2A 1976TT genotype on increased startle response dependent on caffeine intervention and anxiety-related emotional stimulation is in accordance with a higher prevalence and also a higher heritability of AS or anxiety disorders, respectively, in female patients (Jang et al, 1999;Weissman et al, 1997) as well as with previous genetic findings restricted to female patients with anxiety and affective disorders (eg, Deckert et al, 1999;Domschke et al, 2004Domschke et al, , 2007Domschke et al, , 2008a). Also, there are first reports of a potentially gender-differential effect of caffeine in animal models as well as in humans, with, however, still inconsistent conclusions (eg, Botella and Parra, 2003;Fisher and Guillet, 1997;Noschang et al, 2009).…”
Section: Discussionsupporting
confidence: 83%
“…This finding is in line with previous molecular genetic reports of female-specific association findings in panic disorder possibly through hormonal interactions or female-specific transcriptional patterns. [50][51][52] From an evolutionary perspective, one might speculate that the evolutionarily 'newer' T allele variant might convey a beneficial effect by optimizing the fight-or-flight reaction through increased arousal levels, which might be positive in more maledominant predatory environments such as hunting, but not in comparatively safe agricultural or household environments. The present female-dominant finding is contrary to the observation by Okamura et al 27 who reported an association of NPSR rs324981 with panic disorder in the male subgroup of patients only.…”
Section: Discussionmentioning
confidence: 99%
“…In primates, Y 5 receptors are implicated as part of a "stress-sensitive" molecular signature, in that rhesus monkeys exposed to intermittent social stress-induced episodes of hypercortisolism showed an 18% decrease of Y 5 gene expression in prefrontal cortex (Karssen et al, 2007). In human subjects, a clinical study of 230 patients revealed a significant association of Y 5 receptor variants and haplotypes with panic disorder, particularly in females with concurrent agoraphobia (Domschke et al, 2008). Finally, although clinical trials of obese human subjects showed only a small reduction in body weight after treatment with the Y 5 antagonist MK-0557 (Erondu et al, 2006), it is interesting to consider whether Y 5 antagonism might be more effective for obese subjects with eating disorders linked to anxiety or depression.…”
Section: Discussionmentioning
confidence: 99%